‘VirSbud’ as a tool for enhancing students'confidence to speak - Radzuwan, Ab Rashid; Mohd Fazry, A. Rahman; Saiful Bahri, Mohamed (2016)
This interdisciplinary study integrates ICT in education through the creation of a virtual buddy (VirSBud) system as a tool to enhance English language speaking skills among less proficient students. Drawing on the sociocultural perspective of learning, the 'VirSBud' has been developed and tested with a group of participants which consists of five primary school students and an English language teacher. The teacher was briefed of her role as a facilitator before the students were exposed to VirSBud for eight weeks. Adopting one group pre-test and post-test experimental design as its methodology, the teacher was asked to evaluate the students' level of confidence to speak prior to and after their engagement with the VirSBud. The teacher was also interviewed to obtain her feedback on VirSbud whilst the students were asked to complete the Personal Report of Confidence (PRC). The analysis reveals that all the students developed higher confidence level after their engagement with VirBud and the teacher perceived it positively which suggests its potential to be used as a tool in developing speaking skills among less proficient students.